(untitled) (Research, Society and Development, 2022)
Nursing is considered an essential and central profession in the structure of health professions, present in all organizational units of the health system. Occupational risks are all work situations that can disrupt people’s physical, mental and social balance, and not just situations that cause accidents and illness. The occupational risks to which nursing workers are exposed can be characterized as physical, chemical, biological, accidental and ergonomic. In this sense, the article aims to describe the occupational health risks of nursing professionals in the neonatal ICU. This is a bibliographic research with a qualitative approach. Data were collected in a virtual database. For this purpose, the VHL was used, in the following information base: LILACS; BDENF and MEDLINE. After the reflective reading, two categories emerged: Main adverse events in the neonatal ICU; The nursing professional in the prevention of occupational risks. It is concluded that Nursing workers, for playing their role mostly in health units, are exposed to risks present in the environment itself, due to the lack of guidance on the risks of the environment, as well as on the precautions that must be taken to avoid accidents.